The upper Coniacian to upper Santonian drowned Arabian carbonate platform, the Mardin-Mazidag area, SE Turkey: Sedimentological, stratigraphic, and ichthyofaunal records - Yılmaz, İsmail Ömer; Cook, Todd D.; Hosgor, Izzet; Wagreich, Michael; Rebman, Katherine; Murray, Alison M. (Cretaceous Research, 2018)
A measured stratigraphic section including the upper Coniacian - upper Santonian interval in the Mardin-Mazidag area in Southeastern Turkey lies on the Arabian Platform and documents the drowning of the Arabian platform. The studied succession transgressively overlies the exposed carbonate platform and exhibits a relatively condensed sequence characterized by presence of fish remains, phosphate nodules, oncoids, phosphatic fragments, glauconites and planktonic foraminifera. Calcareous nanno-fossils attest a late Coniacian to late Santonian age (zones UC11 - UC12). Numerous elasmobranch teeth are also present in this pelagic fades, representing mackerel sharks (Squalicorax, Pseudocorax and Scapanorhynchus) and a ray (Ctenopristis). The presence of pelagic facies and phosphate deposits on the drowned platform may indicate a sudden rise of sea level and increase of nutrient due to upwelling currents. The collapse parts of the Arabian carbonate platform occurred earlier than previously reported, starting from late Coniacian-Santonian onwards.